Prevalence, Risk Factors, and Clinical Outcomes with Advanced HIV Disease Among People with Newly Diagnosed HIV During the “Treat-All” Era: A Retrospective Cohort Study From Xi’an City, China - Jin J; Pan S; Chen J; Yin J; Ba H; Hou H; Zhang Y; Ma K (Infection and Drug Resistance)
Juan Jin,1,* Songnan Pan,2,* Jie Chen,1 Jinling Yin,1 Huanhuan Ba,1 Haohua Hou,1 Yuan Zhang,1 Kangxiao Ma1 1Department of Infectious Diseases, Xi’an Eighth’s Hospital, Xi’an, Shaanxi, People’s Republic of China; 2Department of Infectious Diseases, Infectious Disease Hospital of Heilongjiang Province, Harbin, Heilongjiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Kangxiao Ma, Department of Infectious Diseases, Xi’an Eighth’s Hospital, 2 Zhangba East Road, Yanta District, Xi’an, Shaanxi, 710061, People’s Republic of China, Tel/Fax +86 029 85393973, Email kbdmzjj@163.comPurpose: China launched “treat-all” in 2016 to make all HIV-positive people eligible for ART regardless of disease stage. Widespread treatment may not eliminate advanced HIV. This study investigated the prevalence, characteristics, risk factors, and clinical outcomes of advanced HIV disease (AHD) in newly diagnosed HIV-positive individuals in China during the “treat-all” period.Patients and methods: We performed a retrospective cohort study on newly diagnosed adult ART-naive people with HIV (PWH) in Xi’an from 2016 to 2022. The prevalence of AHD and six-month mortality/loss to follow-up (LTFU) were investigated. Risk variables for AHD and predictors of mortality or LTFU in the cohort were investigated using multivariate logistic and Cox regression, respectively.Results: Of the PWH, 47.5% (2999/6318) had AHD at HIV diagnosis. At enrollment, being ≥ 50 years (aOR: 1.75, 95% CI: 1.44– 2.12, P < 0.001; ≥ 50 vs 18– 29), 30– 49 years (aOR: 1.43, 95% CI: 1.24– 1.65, P < 0.001; 30– 49 vs 18– 29), opportunity infections (aOR: 7.43, 95% CI: 5.96– 9.35, P < 0.001), severe anemia (aOR: 3.56, 95% CI: 1.81– 7.70, P = 0.001) and liver disease (aOR: 3.09, 95% CI: 1.48– 7.05, P = 0.004) were independently associated with AHD. Within 6 months of enrollment, 95.6% and 58.3% of those who died or were LTFU had AHD. AHD (aHR: 14.30, 95% CI: 4.42– 46.30, P < 0.001), ≥ 50 years (aHR: 5.39, 95% CI: 2.10– 13.82, P < 0.001; ≥ 50 years vs 18– 29 years), those with opportunistic infections (aHR: 2.59, 95% CI: 1.54– 4.34, P < 0.001), and severe anemia (aHR: 9.89, 95% CI: 5.19– 18.87, P < 0.001) were independent predictors of six-month mortality.Conclusion: Under the “treat-all” policy, Xi’an had a high prevalence of AHD upon HIV diagnosis. AHD predicted 6-month mortality. Urgent implementation of targeted strategies is necessary to minimize AHD.Keywords: advanced HIV disease, HIV, mortality, loss to follow-up, treat all, China